Safety and Pharmacokinetics of HRS-2261, a P2X3 Receptor Antagonist, in Healthy Subjects: A Randomized, Double-Blind, Placebo-Controlled Phase 1 Study - Fan, Yuru; Zhang, Xuan; Zhang, Qin; Zheng, Liang; Zhou, Renpeng; Sun, Cheng; Wang, Xihan; Song, Ke; He, Zhusheng; Wang, Honghui; Zhang, Qian; Hu, Wei (Clinical pharmacokinetics, 2024)
Background P2X3 receptor antagonists hold promising potential as a therapeutic option for patients with refractory or unexplained chronic cough, a condition lacking approved therapies. This study assessed the safety, tolerability, and pharmacokinetics (PK) of HRS-2261, a novel selective P2X3 receptor antagonist, in healthy subjects. Methods This randomized, double-blinded, placebo-controlled phase 1 trial of HRS-2261 consisted of three phases: the single ascending dose (SAD) study phase, the food-effect study phase, and the multiple ascending dose (MAD) study phase. In the SAD phase, healthy subjects were randomly assigned to receive a single oral dose of HRS-2261 (25, 100, 200, 400, 800, and 1200 mg) or placebo. Subjects in the 200 mg group of the SAD phase progressed directly to the food-effect phase following safety evaluation. In the MAD phase, healthy subjects were randomized to receive HRS-2261 (50, 200, and 400 mg) or placebo twice daily for 14 consecutive days. The primary endpoints were safety and tolerability. Results A total of 62 and 30 subjects were enrolled in the SAD and MAD phases, respectively, with 12 subjects from the SAD phase transitioning to the food-effect phase. The incidence and severity of adverse events (AEs) were not dose dependent, and most AEs were mild except for one moderate AE (epididymitis, which was not related to treatment) in the 400 mg group. Dysgeusia was reported in nine subjects, including two from the SAD phase, one from the food-effect phase, and six from the MAD phase. The median T max and geometric mean t 1/2 were 0.9–2.0 h and 4.1–8.5 h in the SAD, and 2.0–2.7 h and 4.6–5.0 h on day 14 in the MAD, respectively. Drug exposures in the SAD and MAD phases were both less than dose proportional. The accumulation of the drug was slight with repeated twice-daily dosing. Food-effect study results showed that food intake did not affect the plasma exposure of HRS-2261. Conclusions HRS-2261 demonstrated good tolerability, with a low incidence of dysgeusia. The PK profile was favorable. This study supports further development of HRS-2261 as a potential P2X3 receptor antagonist for chronic cough. Trial Registration Number Clinical trials.gov, identifier: NCT05274516. Trial registration date: March 10, 2022.